2009
DOI: 10.1038/cdd.2009.25
|View full text |Cite
|
Sign up to set email alerts
|

The α/β carboxy-terminal domains of p63 are required for skin and limb development. New insights from the Brdm2 mouse which is not a complete p63 knockout but expresses p63 γ-like proteins

Abstract: p63, an ancestral transcription factor of the p53 family, has three C-terminal isoforms whose relative in vivo functions are elusive. The p63 gene is essential for skin and limb development, as vividly shown by two independent global knockout mouse models. Both strains, although constructed differently, have identical and severe phenotypes, characterized by absent epidermis and hindlimbs and only rudimentary forelimbs at birth. Here we show that mice from one model, Brdm2, express normal levels of truncated p6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…Heterozygous mutations in p63 underlie 7 autosomal-dominant developmental disorders that are characterized by varying combinations of cleft lip, cleft palate, ectodermal dysplasia, and limb abnormalities (7). To date, 2 mouse models of p63 have been reported, one a loss-offunction allele (23) and another recently found to express p63γ isoforms (24,25). Both mouse models exhibit a similar phenotype consisting of severe limb abnormalities, a thin and undifferentiated epidermis, and lack of epidermal derivatives (23,24).…”
Section: Introductionmentioning
confidence: 98%
“…Heterozygous mutations in p63 underlie 7 autosomal-dominant developmental disorders that are characterized by varying combinations of cleft lip, cleft palate, ectodermal dysplasia, and limb abnormalities (7). To date, 2 mouse models of p63 have been reported, one a loss-offunction allele (23) and another recently found to express p63γ isoforms (24,25). Both mouse models exhibit a similar phenotype consisting of severe limb abnormalities, a thin and undifferentiated epidermis, and lack of epidermal derivatives (23,24).…”
Section: Introductionmentioning
confidence: 98%
“…In summary, although the overall outcome of the Brdm2 mice analyzed by Wolff et al 4 are not different from those originally described in the original Mills et al…”
mentioning
confidence: 80%
“…5 However, this issue remains to be determined. In summary, although the overall outcome of the Brdm2 mice analyzed by Wolff et al 4 are not different from those originally described in the original Mills et al 2 paper, and later confirmed in several publications, the differences are numerous enough to potentially generate a considerable degree of confusion in the field. It is possible that the low p63 mRNA and protein levels were simply missed in the earlier papers, because of technical reasons.…”
mentioning
confidence: 82%
See 2 more Smart Citations